Flexural Behavior of UHPC Beams Reinforced with Macro-Steel Fibers and Different Ratios of Steel and GFRP Bars - Yousef Abbasi Parvin; Taleb Moradi Shaghaghi; Masoud Pourbaba; Seyed Saeed Mirrezaei; Yousef Zandi (Journal of Rehabilitation in Civil Engineering)
The flexural and shear behavior of ultra-high-performance fiber-reinforced concrete (UHPFRC) reinforced with different ratios of glass-fiber-reinforced polymer (GFRP) and conventional steel rebars is experimentally studied in this paper. For this purpose, three beams with dimensions of 250 300 1650 mm were reinforced with GFRP rebars in three different ratios (0.64%, 1.05%, and 1.45%) and hooked-end (H) steel fibers by 2% volumetric ratio. Similar procedure was carried for beams reinforced with conventional rebars. Additionally, Nonlinear regression analyses were also carried out to simulate the flexural load-deflection behavior of the beams. Results showed that the role of hooked-end fibers in compensating for the brittle nature of GFRP rebars was insignificant. Besides, increase of the longitudinal reinforcement ratio changed the failure mode from flexural to shear failure in specimens with GFRP rebars. Finally, nonlinear regression models were proposed that successfully capture the load-deflection behavior of the test specimens with coefficient of correlation ( ) very close to unity.